Long-Term Follow-Up of Resistance-Associated Substitutions in Hepatitis C Virus in Patients in Which Direct Acting Antiviral-Based Therapy Failed - Kanako Yoshida (International Journal of Molecular Sciences, 2017)
We evaluated the transition of dominant resistance-associated substitutions (RASs) in hepatitis C virus during long-term follow-up after the failure of DAAs (direct acting antivirals)-based therapy. RASs in non-structure (NS)3/4A, NS5A, NS5B, and deletions in NS5A from 20 patients who failed simeprevir/pegylated-interferon/ribavirin (SMV/PEG-IFN/RBV) and 25 patients who failed daclatasvir/asunaprevir (DCV/ASV) treatment were examined by direct sequencing. With respect to SMV/PEG-IFN/RBV treatment, RAS was detected at D168 in NS3/4A but not detected in NS5A and NS5B at treatment failure in 16 of 20 patients. During the median follow-up period of 64 weeks, the RAS at D168 became less dominant in 9 of 16 patients. Among 25 DCV/ASV failures, RASs at D168, L31, and Y93 were found in 57.1%, 72.2%, and 76.9%, respectively. NS5A deletions were detected in 3 of 10 patients treated previously with SMV/PEG-IFN/RBV. The number of RASs in the breakthrough patients exceeded that in relapsers (mean 3.9 vs. 2.7, p < 0.05). RAS at D168 in NS3/4A became less dominant in 6 of 15 patients within 80 weeks. Y93H emerged at the time of relapse, then decreased gradually by 99% at 130 weeks post-treatment. Emerged RASs were associated with the clinical course of treatment and could not be detected during longer follow-up.